Why high cholesterol levels help hematological malignancies: role of nuclear lipid microdomains. Issue 1 (December 2016) - Codini, Michela; Cataldi, Samuela; Lazzarini, Andrea; Tasegian, Anna; Ceccarini, Maria; Floridi, Alessandro; Lazzarini, Remo; Ambesi-Impiombato, Francesco; Curcio, Francesco; Beccari, Tommaso; Albi, Elisabetta
Abstract Background Diet and obesity are recognized in the scientific literature as important risk factors for cancer development and progression. Hypercholesterolemia facilitates lymphoma lymphoblastic cell growth and in time turns in hypocholesterolemia that is a sign of tumour progression. The present study examined how and where the cholesterol acts in cancer cells when you reproduce in vitro an in vivo hypercholesterolemia condition. Methods We used non-Hodgkin's T cell human lymphoblastic lymphoma (SUP-T1 cell line) and we studied cell morphology, aggressiveness, gene expression for antioxidant proteins, polynucleotide kinase/phosphatase and actin, cholesterol and sphingomyelin content and finally sphingomyelinase activity in whole cells, nuclei and nuclear lipid microdomains. Results We found that cholesterol changes cancer cell morphology with the appearance of protrusions together to the down expression of β-actin gene and reduction of β-actin protein. The lipid influences SUP-T1 cell aggressiveness since stimulates DNA and RNA synthesis for cell proliferation and increases raf1 and E-cadherin, molecules involved in invasion and migration of cancer cells. Cholesterol does not change GRX2 expression but it overexpresses SOD1, SOD2, CCS, PRDX1, GSR, GSS, CAT and PNKP. We suggest that cholesterol reaches the nucleus and increases the nuclear lipid microdomains known to act as platform for chromatin anchoring and gene expression. Conclusion The results imply that, in hypercholesterolemia conditions, cholesterol reaches the nuclear lipid microdomains where activates gene expression coding for antioxidant proteins. We propose the cholesterolemia as useful parameter to monitor in patients with cancer.